Anti-inflammatory potential of selected medicinal plants used in the treatment of sexually transmitted infections and 1H NMR-based metabolomics of Lannea schweinfurthii - Tshikalange, T.E. (Thilivhali Emmanuel) (University of Pretoria, 2020)
Thesis (PhD (Plant Sciences))--University of Pretoria, 2020.